50th birthday of Ralph Kenna - Personalia (Condensed Matter Physics, 2014)
On August 27th, 2014 Ralph Kenna - member of the Editorial Board of "Condensed Matter Physics" and renowned expert in the fields of statistical physics and complex systems - celebrated his 50th birthday.